Crystallinity Improvement of Co3O4 by Adding Thiourea - Kaygılı, Omer; Bulut, Niyazi; Yahıa, I.s.; Ercan, İsmail; Ercan, Filiz Altıparmak; Ates, Tankut; Mahmood, Bahroz (My University, 2020)
Tricobalt tetraoxide (Co3O4) samples having different thiourea/Co molar ratio of 0, 5 and 10 were prepared by wetchemical synthesis. The effects of thiourea content on the crystal structure-related parameters of Co3O4 weredetermined. The increase in the amount of thiourea caused a gradual decrease in the lattice parameters and specificsurface area and an increase in the crystallinity and crystallite size. The experimental analysis results showed thatthiourea content can be used to control the crystal structure-related parameters of Co3O4.
Keywords: Mühendislik; Kimya